2022
DOI: 10.4103/sjmms.sjmms_141_22
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Late DNR Orders and its Predictors in a Saudi Arabian ICU

Abstract: Background Practices of Do-Not-Resuscitate (DNR) orders show discrepancies worldwide, but there are only few such studies from Saudi Arabia. Objective: To describe the practice of DNR orders in a Saudi Arabian tertiary care ICU. Methods: This retrospective study included all patients who died with a DNR order at the ICU of King Saud Medical City, Riyadh, Saudi Arabia, between January 1 to December 31, 2021. The percentage of early DNR (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…In the current study, DNR orders were implemented in 13% of patients in the ICU. This rate is similar to what had been observed in other studies from different countries, including Saudi Arabia [ 17 , 18 ]. In an international study, a decision to withhold/withdraw life support during the ICU stay was reported in 1259/9524 (13%) patients [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, DNR orders were implemented in 13% of patients in the ICU. This rate is similar to what had been observed in other studies from different countries, including Saudi Arabia [ 17 , 18 ]. In an international study, a decision to withhold/withdraw life support during the ICU stay was reported in 1259/9524 (13%) patients [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that 55% of the deceased patients in the ICU had DNR orders before death. This rate is lower than that reported in other studies [ 18 , 25 ]. In a study of a large US sample of ICU patients (400129 admissions, 9891 deaths in the ICU), 91.3% of patients had DNR order before death [ 25 ].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…On the other hand, 41% of the participating physicians ever had their patients have "advanced directive" or "living will". As indicated in other studies from Saudi Arabia [18,22,26], the majority of participating physicians are looking for additional learning materials and training related to DNR decision-making and ELMC as what is become standard practice to have a continuous professional development program for basic life support (BLS) is to have ELMC and DNR program. There is also a need for proper and new guidelines to deliver standardization of DNR practices and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 ] Additionally, there is no consensus on medical futility [ 12 ] or guidance on the practical aspects of the DNR process, such as objective criteria. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%